Modification of Traffic-related Respiratory Response by Asthma Control in a Population of Car Commuters. Issue 4 (July 2015) - Mirabelli, Maria C.; Golan, Rachel; Greenwald, Roby; Raysoni, Amit U.; Holguin, Fernando; Kewada, Priya; Winquist, Andrea; Flanders, W. Dana; Sarnat, Jeremy A.
<x xml:space="preserve">Abstract</x> Background: Effects of traffic-related exposures on respiratory health are well documented, but little information is available about whether asthma control influences individual susceptibility. We analyzed data from the Atlanta Commuter Exposure study to evaluate modification of associations between rush-hour commuting, in- vehicle air pollution, and selected respiratory health outcomes by asthma control status. Methods: Between 2009 and 2011, 39 adults participated in Atlanta Commuter Exposure, and each conducted two scripted rush-hour highway commutes. In-vehicle particulate components were measured during all commutes. Among adults with asthma, we evaluated asthma control by questionnaire and spirometry. Exhaled nitric oxide, forced expiratory volume in 1 second (FEV1), and other metrics of respiratory health were measured precommute and 0, 1, 2, and 3 hours postcommute. We used mixed effects linear regression to evaluate associations between commute-related exposures and postcommute changes in metrics of respiratory health by level of asthma control. Results: We observed increased exhaled nitric oxide across all levels of asthma control compared with precommute measurements, with largest postcommute increases observed among participants with below-median asthma control (2 hours postcommute: 14.6% [95% confidence interval CI = 5.7, 24.2]; 3 hours postcommute: 19.5% [95% CI = 7.8, 32.5]). No associations between in-vehicle pollutants and percent of predicted FEV1 were observed, although higher PM2.5 was associated with lower FEV1 % predicted among participants with below-median asthma control (3 hours postcommute: –7.2 [95% CI = –11.8, –2.7]). Conclusions: Level of asthma control may influence respiratory response to in-vehicle exposures experienced during rush-hour commuting.